2022
DOI: 10.3390/brainsci12020295
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Spasticity across Time in Prolonged Disorders of Consciousness: A Retrospective Study

Abstract: Objectives: In this retrospective study, we investigated how spasticity developed in patients diagnosed with a prolonged DOC over an almost two-year observation period (21 months), and how it related to the patients’ age, gender, time since injury, etiology, level of consciousness, and anti-spastic medications. Methods: In total, 19 patients with a severe brain injury and prolonged DOC admitted to a long-term care facility were included in this study (14 male, age: 45.8 ± 15.3 years, 10 traumatic brain injury,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Indeed, in our cohort, younger age, hemisyndrome, and tetraparesis were potentially important predictors of severer neck muscle spasticity in MCS patients, while severe spasticity was a predictor of worse neurological and functional outcome at discharge in UWS patients, independently of other confounding variables such as sex, age, and the severity of neurological and functional assessment at admission. These findings are in line with a recent retrospective 7 study which suggested that spasticity evolves differently according to the etiology of the brain lesion and the level of consciousness.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Indeed, in our cohort, younger age, hemisyndrome, and tetraparesis were potentially important predictors of severer neck muscle spasticity in MCS patients, while severe spasticity was a predictor of worse neurological and functional outcome at discharge in UWS patients, independently of other confounding variables such as sex, age, and the severity of neurological and functional assessment at admission. These findings are in line with a recent retrospective 7 study which suggested that spasticity evolves differently according to the etiology of the brain lesion and the level of consciousness.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies examining spasticity in DOC reported a prevalence ranging from 59% to 89%. 5 - 7 , 16 Indeed, spasticity is one of the commonest complications following severe brain injury, due to the broad distribution and extent of brain damage at various levels of the central nervous system (cortical, infra-cortical and spinal). 5 , 6 As expected, we found that UWV patients presented worse CRS-R and GCS scores on admission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the evolution of spastic paresis, a recent longitudinal study in patients with prolonged DoC (> 12 month post injury), showed that both the aetiology and the diagnosis seem to influence the development of spasticity over time. Indeed, the authors found that in TBI patients, spasticity (upper limb) tended to increase in a delayed manner compared to non-TBI aetiologies (Winters et al, 2022).…”
Section: Spastic Paresis In Docmentioning
confidence: 99%
“…The main causes of severe motor disabilities in patients with DoC consist of diffuse spastic paresis (Thibaut et al, 2014;Winters et al, 2022;Zhang et al, 2021), commonly associated with pathological postures, such as decortication and decerebration (Dolce et al, 2002). Spastic paresis is often linked to pain perception and hyperpathia, which may impact patients' quality of life (Bargellesi et al, 2018;Thibaut et al, 2014;Zasler, Formisano, & Aloisi, 2022).…”
Section: Introductionmentioning
confidence: 99%